Profiles of apple allergen components and its diagnostic value in Northern China - Wang, Xiaoyan; Chen, Lijia; Lan, Tianfei; Wang, Hongtian; Wang, Xueyan (Frontiers in Medicine, 2024)
Background: Limited is known on the profiles of apple allergy in China. Objective:To explore the clinical significance of apple allergen components in northern China.: This study recruited 40 participants and categorized into apple tolerance (n=19) and allergy (n=21) group. The latter was categorized into oral allergy symptoms (OAS, n=14) and generalized symptoms (GS, n=7). All participants underwent ImmunoCAP screening to assess sIgE levels of birch, apple, and their components. Results: The sensitization rates were 90% for Bet v 1, 85% for Mal d 1, 35% for Bet v 2, and 20% for Mal d 3. The overall positive rate for apple allergens was 97.5%, with half demonstrating mono-sensitization to Mal d 1. Birch, Bet v 1 and Mal d 1 sIgE levels had consistent areas under the curve (AUC 0.747, p=0.037; AUC 0.799, p=0.012; AUC 0.902, p<0.001 respectively) in diagnosing apple allergy. The optimal cut-off values were determined to be 22.85 kUA/L (63.6% sensitivity, 85.7% specificity), 6.84 kUA/L (81.8% sensitivity, 71.4% specificity) and 1.61 kUA/L (93.8% sensitivity, 75.0% specificity), respectively. No allergens or components demonstrated diagnostic value in distinguishing between OAS and GS. Mal d 3 sensitization was correlated with mugwort allergy and higher risk of peach, nuts or legumes generalized allergy. Conclusion: Mal d 1 was major allergen and the best for diagnosing apple allergy. Mal d 3 does not necessarily indicate severe allergic reaction to apples in northern China but may indicate mugwort sensitization and an increased risk of peach, nuts or legumes allergy.